Assessment and Evaluation of Madiredo Telaga Tourism Service Factors - Psf, Muhammad Ivan Riyandhika Saad; Wicaksono, Agus Dwi; Adrianto, Dimas Wisnu (Journal of Regional and Rural Studies, 2024)
This study introduces the "FIPIA with information entropy" method as an evolution of previous models (IPA, IPIA, FIPA) to evaluate the quality of tourism services at Telaga Madiredo. The aim is to identify priority areas for improvement, providing actionable recommendations for optimal resource allocation to enhance customer service and satisfaction. The integration of fuzzy rules and expert assessments reduces subjectivity in evaluation. Despite its rich potential as a nature-based tourism destination, Madiredo Agrotourism faces challenges due to insufficient prioritization and evaluation of services, leading to a gap between tourist expectations and actual service quality. The primary goal is to develop a comprehensive plan for improving tourism services aligned with on-ground realities and critical priorities. This is achieved through three parameters: comparing importance and performance of service attributes, assessing their impact on business objectives, and evaluating their importance for tourist satisfaction. The study involved field testing by distributing a questionnaire with 18 items to Madiredo Lake tourists and analyzing responses using Importance-Performance-Impact Analysis (IPIA), fuzzy logic, and information entropy. The findings revealed five key dimensions of service quality: reliability, assurance, tangibles, empathy, and responsiveness. The FIPIA method with information entropy proved effective for prioritizing service improvements and is adaptable for evaluating service quality across various industries where attributes significantly influence outcomes.